DESIGN OF HARDWARE-IN-THE-LOOP-SIMULATION FOR EDF ROCKET CONTROL SYSTEM DEVELOPMENT - AULIA YULNANDI (NIM : 23215146), REZA
Hardware-in-the-Loop-Simulation (HILS) is method to reduce time and cost of control system development with intergrate hardware to simulation system. Several studies shown that HILS can improve success probability in term control and safety on flight testing rocket. HILS systems are mostly consist of manufactured controller hardware and simulator software. Both of them are generally not open-source. Moreover, implementing HILS by using manufactured system for simple guidance rocket is costly. This thesis deals with design and implementation process of HILS for Electric Ducted Fan (EDF) rocket development by using open-source platform with middleware. This middleware system has few task i.e bridge controller hardware to simulator software (vice versa), data flow control and provide human-machine interface. A low cost 8-bit microcontroller is used as controller hardware. ATMEGA 2560 series microcontroller is used to calculate rocket’s attitude with Direction Cosine Matrix (DCM) algorithm and implementing PID controller is employed to regulate rocket’s dynamics based on desired specifications. X-Plane version 10 is used as simulator software for designing 3 dimension EDF rocket model and generating simulated sensory data. The test results validate that HILS design meets the defined specifications, i.e. angle difference of 0.36 degrees in attitude calculating process and rise time of 0.149 seconds on pitch angle.